Immigrer, mourir et vivre un deuil au Canada : contexte légal, stratégies et réseaux transnationaux - Lilyane Rachédi Drapeau; Laura Cheron-Leboeuf; Béatrice Halsouet; Michèle Vatz-Laaroussi (IdeAs)
This text presents death and mourning in a migration context. It is based on two qualitative researches that were conducted in the province of Quebec, Canada. The first one interviewed bereaved men and women and key informants from Christian, Muslim and Hindu traditions. The second one was interested in intergenerational transmissions de generational trios of women who migrated as refugees. The principal results emphasize the importance of funeral rituals when the loss of a loved person occurs in the host country. Nevertheless, respecting and putting into practice these rituals is conditional to the legal context of the host country. The bereaved persons adapt to it and develop strategies in order to maintain the most significant practices. The refugee women's discourse stimulates another conception of the investment in transnational networks and the migration when death -occurs.